2008
DOI: 10.4319/lo.2008.53.6.2558
|View full text |Cite
|
Sign up to set email alerts
|

Assimilatory uptake rather than nitrification and denitrification determines nitrogen removal patterns in streams of varying land use

Abstract: Agricultural and urban land use increase nitrogen (N) concentrations in streams, which can saturate biotic demand by plants, algae, and bacteria via assimilative uptake, and by nitrification and denitrification. We studied six streams per year in each of three land-use categories (agricultural, urban, and forested) for 3 yr (n 5 18 streams), and we compared whole-stream N uptake and microbial N transformation rates during spring, summer, and autumn. We measured whole-stream removal of added ammonium (NH , nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
47
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 55 publications
4
47
0
Order By: Relevance
“…denitrification and DNRA) such as oxygen conditions (water column DO concentrations) and organic carbon (benthic organic matter content) (Tiedje 1988), although U did increase in response to lower DO concentrations. This suggests that much of the demand for NO 3 ( in the Taupo streams during summer was probably assimilatory and is consistent with other studies showing that assimilatory processes tend to dominate instream NO 3 ( uptake (Mulholland et al 2004(Mulholland et al , 2008Arango et al 2008).…”
Section: Discussionsupporting
confidence: 78%
“…denitrification and DNRA) such as oxygen conditions (water column DO concentrations) and organic carbon (benthic organic matter content) (Tiedje 1988), although U did increase in response to lower DO concentrations. This suggests that much of the demand for NO 3 ( in the Taupo streams during summer was probably assimilatory and is consistent with other studies showing that assimilatory processes tend to dominate instream NO 3 ( uptake (Mulholland et al 2004(Mulholland et al , 2008Arango et al 2008).…”
Section: Discussionsupporting
confidence: 78%
“…Others have found that biotic assimilation represented a substantial portion of the nitrate uptake in various aquatic systems (Webster et al 2003;Mulholland et al 2004;Arango et al 2008). Rates of biotic N uptake, standing stock, and turnover were not quantified in Second Lake.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to measure both ecosystem metabolism and nutrient dynamics at comparable temporal scales for whole stream ecosystems has provided elegant demonstrations of the direct coupling between nitrogen cycling and metabolism (e.g., Hall and Tank 2003, Hall et al 2009). Streams have also provided more nuanced understanding of the indirect effects of metabolism on N assimilation and denitrification (Hoellein et al 2007, Arango et al 2008, Mulholland et al 2008, as well as the coupling of N and P cycles (Cross et al 2005, Schade et al 2011.…”
Section: Introductionmentioning
confidence: 99%